Numerical analysis for attenuation effects of perforated plates on thermoacoustic instability in the multiple flame combustor. (5th March 2018) - Kwon, Minjun; Oh, Seungtaek; Kim, Yongmo
Highlights: FDF-based approach with a Helmholtz solver is utilized to analyze combustion instability. New optimizing method the perforated plate using Luong model has been proposed. Attenuation characteristics of single and dual perforated plates are numerically analyzed. Abstract: In the present study, the FDF-based approach together with the Helmholtz solver has been applied to precisely analyze the attenuation effects of the perforated plates on thermoacoustic instability in the lab-scale multiple flame combustor. In order to effectively suppress the combustion instability, we derive the optimal damping conditions for perforated plates in terms of the porosity and cavity length. To overcome the weaknesses of the Howe model, the Luong model is utilized for an impedance boundary condition of perforated plates. After then, we validated our methodology to the impedance tube, which shows the predicted results are well agreed with the experimental data for all validation cases Another new approach for the dual perforated plates has been proposed to enlarge the absorption bandwidth in a wider frequency regime. Numerical results clearly indicate that since the dual plates are tuned at two different target frequencies, the system can have two maximum absorption points and their combined effects in a frequency range. This makes the dual-plate method capable of stabilizing the combustion instability in the much wider frequency range than does the single-plate scheme. Therefore, it is expected that the dual-plate methodology would be more effective to suppress the unexpected nonlinear behavior such as the mode change, frequency shift, and hysteresis thanks to the wide attenuation coverage.